Multimodal scaffolding in critical reading: Pedagogical insights from Indonesian EFL learners - Arum Puspitasari; Moh. Kholilurrahman Jailani; Yazid Basthomi; Suharyadi Suharyadi; Evynurul Laily Zen (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
Scaffolding through multimodality is increasingly popular inEnglish as a Foreign Language (EFL) settings, providing newopportunities for critical reading proficiency creation withvisual, audio, and text resources. Thus, this study examines thephenomena of multimodal scaffolding among Indonesian EFLundergraduate learners in a tertiary reading course, the criticalreading course. The study used a descriptive qualitativeresearch design, collecting data from 29 English LanguageTeaching (ELT) major students through reflective journals, focusgroup discussions, and classroom observation notes to gain indepthinsights into their experiences and perspectives.Through thematic analysis approach, several themes werefound from participants' reflections and discussions: (1)multimodal texts promoted student engagement and sustainedinterest; (2) visual and audio elements facilitatedcomprehension of abstract/intricate concepts; and (3) the nonlinearcomposition of multimodal texts complicated multimodalanalysis due to limited exposure. The findings reveal thatmultimodality serves as both an effective critical readingscaffold and a cognitive complication for interpretation,meaning that multimodal literacy must be explicitly taught.Ultimately, this study contributes to the research gap in criticalliteracy and multimodal literacy in the EFL higher educationcontext with practical pedagogical recommendations based onthe learner perspective.